2018
DOI: 10.1016/j.jiph.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Rectal swab screening assays of public health importance in molecular diagnostics: Sample adequacy control

Abstract: Rectal swabs are routinely used by public health authorities to screen for multi-drug resistant enteric bacteria including vancomycin-resistant enterococci (VRE) and carbapenem-resistant enterobacteriaceae (CRE). Screening sensitivity can be influenced by the quality of the swabbing, whether performed by the patient (self-swabbing) or a healthcare practitioner. One common exclusion criterion for rectal swabs is absence of "visible soiling" from fecal matter. In our institution, this criterion excludes almost 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Evidence to support the requirement of visible pigment is sparse. In one study, approximately 10% of rectal swab specimens received in the microbiology laboratory were excluded from processing due to the absence of visible pigment (9), and an unknown proportion were not even submitted from the point of collection for similar reasons. The absence of visible pigment on a swab is presumed to indicate that the stool sample on the swab is inadequate, but no published data support the superior sensitivity of swabs with visible feces.…”
mentioning
confidence: 99%
“…Evidence to support the requirement of visible pigment is sparse. In one study, approximately 10% of rectal swab specimens received in the microbiology laboratory were excluded from processing due to the absence of visible pigment (9), and an unknown proportion were not even submitted from the point of collection for similar reasons. The absence of visible pigment on a swab is presumed to indicate that the stool sample on the swab is inadequate, but no published data support the superior sensitivity of swabs with visible feces.…”
mentioning
confidence: 99%
“…Clinical diagnostic guidelines generally assume a positive relationship between visible soiling with fecal matter and the diagnostic utility of rectal swabs. 44 However, recent interrogations of this relationship have concluded that testing rectal swabs that lack visible feces is worthwhile for the PCR detection of common enteric bacteria and viruses. 44,45 Our results further corroborate this conclusion in the context of a protozoan diagnostic, as we observed no difference in rectal swab sensitivity when controlling for visible feces.…”
Section: Discussionmentioning
confidence: 99%
“…44 However, recent interrogations of this relationship have concluded that testing rectal swabs that lack visible feces is worthwhile for the PCR detection of common enteric bacteria and viruses. 44,45 Our results further corroborate this conclusion in the context of a protozoan diagnostic, as we observed no difference in rectal swab sensitivity when controlling for visible feces. There was an indication that C q values were slightly lower in rectal swabs with visible stool, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Described tcdB qPCR assay was validated with multiple commercial assays in the past (C difficile Quick Check Complete, Alere; BD Max, BD and BD GeneOhm, BD) and used over last 10 years in our institution to detect symptomatic patients which are positive for tcdB biomarker. The relative normalization of samples was obtained using universal 16S rDNA amplicons, as a measure of total bacterial load, as described [23]. The qPCR was performed on Roche Light Cycler 480 instrument, following PCR program: hold at 94 o C for 2 minutes and cycling of 45x (94 o C, 10sec, and following by priming, elongation and acquisition of fluorescence at 50 o C for 20 seconds).…”
Section: Methodsmentioning
confidence: 99%